SAT0319 Diagnostic Value of Ultrasound in Calcium Pyrophosphate Deposition Disease: A Systematic Review and Meta-Analysis. (9th June 2015) - Gamon, E.; Mouterde, G.; Barnetche, T.; Combe, B.
Abstract : Background: Calcium Pyrophosphate Deposition (CPPD) is a crystal related arthritis, which can be difficult to diagnose. Conventional radiography is considered as the routine modality to detect cartilage calcification. However, ultrasound (US) is a technique that has recently demonstrated higher sensibility in the detection of CPP crystal deposition.(1) Objectives: To analyze the sensitivity and the specificity of US in CPP crystals deposits detection in knee and cartilages of other joints using microscopic crystal detection as a gold standard by performing a systematic review and meta-analysis based on data from cohort studies. Methods: A systematic review of literature was performed until december 2014. Bibliographic references were selected from Embase, Medline and Cochrane databases, and abstracts from the two last European League Against Rheumatism and American College of rheumatology annual meetings. The reference lists of selected articles were manually searched to identify additional relevant reports. We chose studies reporting performance of US in diagnosis of CPPD. A meta-analysis was then performed, using the inverse variance method to evaluate a global sensibility and specificity of US. Statistical heterogeneity was assessed by Cochran Q-test and I 2 values. Results: The search found out 85 articles and 11 abstracts of which respectively 17 and 4 were selected for analysis. Retrieved data allowed meta-analysis on 4 articles and 4 abstracts for the sensibility and specificity of US. A total of 262 patients with a CPPD disease and 335 controls were included. All CPPD diagnosis were confirmed by microscopic observation. The articular sites studied were mostly knees but also elbows, shoulders, wrists and feet. Included patients had the following features: mean age 49-74 years, male (29-71%). The US patterns researched were: 1) Thin hyperechoic bands in the hyaline cartilage (8 articles) 2) Hyperechoic spots in fibrous cartilage or in tendons (7 articles) 3) Homogeneous hyperechoic nodular localized in bursae or articular recesses (4 articles). The results showed a sensibility ranging from 60% to 100% and a specificity ranging from 39% to 100% according to the selected studies. The meta-analysis revealed a sensibility of 91% (95% CI 87.6 – 94.4) and a specificity of 96.6% (95% CI 94.7 – 98.4) with a heterogeneity of 72.4% and 87.24% respectively in a fixed model. The random model showed a sensibility of 87.9% (95% CI 80.9 – 94.9) and a specificity of 91.5% (95% CI 85.5 – 97.5). Conclusions: The results of this meta-analysis confirm that US has very high sensibility and specificity values and is a promising tool in the diagnosis and management of CPPD. References: Barskova VG, Kudaeva FM, Bozhieva LA, Smirnov AV, Volkov AV, Nasonov EL. Comparison of three imaging techniques in diagnosis of chondrocalcinosis of the knees in calcium pyrophosphate deposition disease. Rheumatol Oxf Engl. 2013 Jun;52(6):1090–4. Disclosure of Interest: None declared